Teachers’ readiness to organize primary school age children research activities - Abildina, S.; Aitzhanova, R.; Kopbalina, K. (KSU Publ., 2018)
The article highlights aspects of the teachers’ readiness to organize research activities such as the theoretical aspect, including the methods and forms of research activity, the practical aspect, involving the use of diagnostic materials and the motivational aspect, which implies readiness for further training in this direction, self-development and cooperation. In the article the levels of theoretical, practical and motivational teacher’s readiness for the organization research activity of primary schoolchildren are investigated. The systematic application effectiveness of a certain training model of primary school teachers to this activity is stressed. On the basis of the conducted research conclusions are formulated, the readiness of teachers for the organization of primary schoolchildren research activity, its levels is analyzed, the basic indicators of these levels are described. The terms «research activity» and «research skills», «readiness» are specified. The results of the questionnaire survey of primary school teachers on the readiness to organize research activities are analyzed and compared. The authors give a comparative analysis of the readiness levels, draws conclusions.
Мұғалімнің төменгі сынып оқушыларының ғылыми-зерттеу қызметін ұйымдастыруға дайындығы
Готовность учителей к организации исследовательской деятельности младших школьников
Keywords: research; intellectual need; research skills; research activity; primary school; research work; research training; professional competence; preparation; qualification; preparation for research